Evidence of dysfunction in the visual association cortex in visual snow syndrome. Issue 6 (30th November 2018) - Eren, Ozan; Rauschel, Veronika; Ruscheweyh, Ruth; Straube, Andreas; Schankin, Christoph J.
Abstract : Patients with visual snow syndrome (VS) suffer from a debilitating continuous visual disturbance of unknown mechanism. The present study tested the hypothesis of dysfunctional visual processing using visual evoked potentials. Eighteen patients were compared to age‐matched migraineurs (M) and healthy controls (C) using 2‐way analysis of variance with group (VS, M, C) and gender as factors. Visual evoked potentials from patients with VS demonstrated increased N145 latency (in milliseconds, VS: 152.7 ± 7.9 vs M: 145.3 ± 9.8 vs C: 145.5 ± 9.4; F  = 3.28; p  = 0.046) and reduced N75–P100 amplitudes (in microvolts, VS: 7.4 ± 3.5 vs M: 12.5 ± 4.7 vs C: 10.8 ± 3.4; F  = 3.16; p  = 0.051). Dunnett post hoc analysis was significant for all comparisons between VS and controls. These findings are in agreement with the idea that the primary disturbance in VS is a dysfunction of the visual association cortex. Ann Neurol 2018;84:946–949